Blood pressure variability associated with in-hospital and 30-day mortality in heart failure patients: a multicenter cohort study - Zhang, Zhiqiang; Tang, Shanshan; Chen, Lei; Zhao, Yangyu; Hu, Tenglong; Sun, Na; Sun, Qiang; Liang, Wenyan; Wei, Xiqing (Scientific reports, 2025)
To investigate the association between blood pressure variability (BPV) and mortality (in-hospital and 30-day) among heart failure (HF) patients, and to examine these associations across patient subgroups. This multicenter retrospective cohort study analyzed 25,591 heart failure patients from two intensive care databases (eICU Collaborative Research Database [eICU-CRD] and the Medical Information Mart for Intensive Care IV [MIMIC-IV]). BPV was assessed using coefficient of variation of systolic (SBPV), diastolic (DBPV), and mean (MBPV) blood pressure measurements. Multivariable logistic regression and Cox proportional hazards models evaluated mortality associations, adjusting for clinical parameters. The observed mortality rates were 14.7% (in-hospital) and 17.3% (30-day). Higher BPV demonstrated significant associations with increased mortality risk, with SBPV showing the strongest relationship. For in-hospital mortality, each standard deviation increase in SBPV, DBPV, and MBPV corresponded to adjusted odds ratios of 1.56 (95% CI 1.51–1.62), 1.21 (95% CI 1.16–1.25), and 1.42 (95% CI 1.37–1.48), respectively. For 30-day mortality, adjusted hazard ratios were 1.37 (95% CI 1.33–1.41) for SBPV, 1.15 (95% CI 1.12–1.19) for DBPV, and 1.30 (95% CI 1.27–1.34) for MBPV. These associations remained robust across all patient subgroups. Increased blood pressure variability during hospitalization independently predicts higher in-hospital (14.7%) and 30-day mortality (17.3%) in HF patients, with SBPV showing the strongest association (OR: 1.56, 95% CI 1.51–1.62). BPV may serve as a valuable prognostic marker for risk stratification in hospitalized heart failure patients.